Α-Well-Posedness for Quasivariational Inequality Problems. (20th May 2012) - Peng, Jian Wen; Tang, Jing
Abstract : We introduce and study the concepts of α -well-posedness and L- α -well-posedness for quasivariational inequality problems having a unique solution and the concepts of α -well-posedness in the generalized sense and L- α -well-posedness in the generalized sense for quasivariational inequality problems having more than one solution. We present some necessary and/or sufficient conditions for the various kinds of well-posedness to occur. Our results generalize and strengthen previously known results for quasivariational inequality problems.